Kompilasi Hukum Ekonomi Syariah dalam Pemaknaan Hukum Islam dan Sistem Hukum Positif Di Indonesia - Ifa Lathifa Fitriani (Supremasi Hukum: Jurnal Kajian Ilmu Hukum, 2016)
Law Number 3 Year 2006 about Alteration of Law Number 7 Year 1989 about Religious Court has given new authority to Religion Court in Islamic economic dispute settlement. In order to fulfill this new authority, Supreme Court of Indonesia makes Sharia Economic Law Compilation (KHES) that used as one of material law resources in Islamic economic dispute settlement by Religion Court. In Islamic law context, Many Muslim scholars often compare position of KHES to Islamic Law Compilation (KHI), fatwa of mufti, and decision of qhadi that are part of fiqh of Indonesia. However, if KHES is seen by legal system of Indonesian perspective, the KHES still uses Supreme Court Rule which has been different in legal binding compared to the other regulations. This position also is considered as one of the factors why the position of KHES in Indonesia still has insignificant of law bargaining position.